THE ROLE OF SCHOOL COMMITTEES IN EDUCATION MARKETING: A QUALITATIVE STUDY OF TEACHER PERSPECTIVE ANALYSTS - Imam Kurniawan; Didin Wahyudin; Rizky Nurfitriani; Rusi Rusmiati Aliyyah (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to explore the role of school committees in educational marketing based on teacher perceptions regarding four aspects of teacher understanding related to the role of education committees, the role of committees in educational marketing, opportunities and challenges of committees in educational marketing. The method used in this study is qualitative. Data collection used open interview techniques with private school teachers in Bogor Regency. Data analysis used the Miles and Huberman model with stages of data collection, data reduction, data presentation, and drawing conclusions and assisted by the NVivo application. Data validity used a credibility approach with source triangulation techniques. The results of the study showed that there were findings of four main aspects, namely teachers' understanding of the role of the committee, the role of the committee in educational marketing, opportunities, and challenges faced. These findings include various strategic functions, such as communication, quality improvement, school promotion, community networks and obstacles in collaboration and HR competency. This study recommends improving the committee recruitment system, improving the competence of the education committee, and active collaboration between schools/institutions and the education committee